Transient CFS Response over a Multilayer Earth - Patra, H.P.; Nimmagadda, Shastri (Narosa Publishing House, 1998)
Transient electromagnetic sounding is successfully applied in mineral and groundwater exploration. Major advantage of the transient sounding is to overcome the effects of conductive overburden where frequency-domain CFS frequently fails. Today time-domain EM sounding is also an important exploration tool to determine the permafrost thickness and for oil exploration in ice covered areas. Fourier transform approach is used for computing the transient response due to different electromagnetic sounding configurations over a multilayer earth (Mallick and Verma, 1978; Patra and Mallick, 1980). Digital linear filter approach is used by Patra and Shastri (1991) for computing transient CFS response due to a two-layer earth. Verma (1977) and Verma and Mallick (1979) have studied the phenomenon of detectability with different layered earth models. Studies are made on CFS transient response in terms of resolution characteristics and performance of transient CFS over multilayer earth models. H and K type three-layer and some four-layer earth models are considered for transient response computation. Different loop radii are also chosen in order to study any significant change in the resolution characteristics for detecting deeper layers. Finally, the applicability of transient CFS over a multilayer earth is briefly mentioned.